PENGARUH KUALITAS PELAYANAN, KEBERAGAMAN MENU, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN ARIESTA SEMARANG - Rafi Oktavianto; Wahyu Hidayat (Universitas Diponegoro, 2019)
The development and competition of the culinary services business is increasing rapidly. They compete in providing the best service to retain their customers. This research was conducted on Angkringan Ariesta semarang. From sales data of Angkringan Ariesta semarang it can be found that there are fluctuations of sales and amount of Angkringan Ariesta semarang consumer’s complaints related service quality and food delicacy. As a micro small business that engaged in service sector, Angkringan Ariesta semarang must provide good service to its customers, good service is equal, menu diversity, and with price according to what is given by Angkringan Ariesta semarang.This study aims to determine the effect of service quality (X1), menu diversity (X2) and price (X3) on consumer purchasing decisions (Y) on Angkringan Ariesta Semarang. Type of research that used is explanatory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 100 respondents Angkringan Ariesta Semarang customers using the Purposive Sampling method. The analysis technique used are validity test, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS 16. From the result of research indicate that service quality have strong influence to purchasing decision equal to 51,5%, while menu diversity have strong influence to purchasing decision equal to 61%, and price influence strong enough to decision of purchase equal to 64,1%. It shows that price variable to purchase decision variable has higher influence than service quality and menu diversity variable. Suggestions that can be given to increase purchasing decisions are Angkringan Ariesta must be brave to compete in providing low prices because they are considered important by consumers, but still lack the attention of micro-small businesses such as price compatibility with the quality of angkringan, a comparison between Ariesta and other equivalent.